IMPROVING STUDENTS’ SPEAKING SKILL THROUGH PROJECT BASED LEARNING (PBL) - Desi Ratna Sari Simbolon; Acep Haryudin; Efransyah Efransyah (IKIP Siliwangi, 2019)
Project Based- Learning (PBL) is one of teaching technique where the students work in group project and it is required students for designing, planning, and carrying out an extended project that produces a publicly- exhibited output such as a product, publication, or presentation. This research used Classrom Action Research as the research method. The sample of this research were 30 students of the tenth grade, Tehnik Instalasi Tenaga Listrik of SMK PGRI 3 CIMAHI. The students assessed by using speaking rubric by Brown 2004. The data were calculated by using SPSS. As the result, the technique can improve the students speaking skill. It is concluded based on data analyzed. In the first cycle, the students categorized as the poor and low English speaking while the second and the third cycle, the students showed a significant achievement and categorized in good average. This technique can be the affective technique that can be used by the teachers who want to improve students’ speaking skill. Keywords: Speaking, Students’ Difficulties, PBL